2016
DOI: 10.1016/j.imlet.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Atypical IκB proteins in immune cell differentiation and function

Abstract: The NF-κB/Rel signalling pathway plays a crucial role in numerous biological processes, including innate and adaptive immunity. NF-κB is a family of transcription factors, whose activity is regulated by the inhibitors of NF-κB (IκB). The IκB proteins comprise two distinct groups, the classical (cytoplasmic) and the atypical (nuclear) IκB proteins. Although the cytoplasmic regulation of NF-κB is well characterised, its nuclear regulation mechanisms remain marginally elucidated. However, work from recent years i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 94 publications
(236 reference statements)
0
56
0
Order By: Relevance
“…Although the downstream mechanism of IκBζ function remains unclear, it is suggested that IκBζ recruits epigenetic factors to the promoter region of its target genes, thereby modulating gene expression (13,14). Induction of IκBζ and subsequent target gene expression has been investigated in different cell types, such as keratinocytes, macrophages, dendritic cells, and T cells (15). Stimulation of keratinocytes with IL-17A or IL-36 induces IκBζ expression, leading to the induction of several psoriasis-associated target genes, such as Cxcl8, Cxcl2, Defb4, or S100a9 (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Although the downstream mechanism of IκBζ function remains unclear, it is suggested that IκBζ recruits epigenetic factors to the promoter region of its target genes, thereby modulating gene expression (13,14). Induction of IκBζ and subsequent target gene expression has been investigated in different cell types, such as keratinocytes, macrophages, dendritic cells, and T cells (15). Stimulation of keratinocytes with IL-17A or IL-36 induces IκBζ expression, leading to the induction of several psoriasis-associated target genes, such as Cxcl8, Cxcl2, Defb4, or S100a9 (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In classical NF‐κB signaling, the NF‐κB transcription factors are rendered transcriptionally inactive through sequestering in the cytoplasm by inhibitors of κB (IκB), such as IκB‐α, IκB‐β, IκB‐ε, and the p50 precursor p105 . In addition to the cytoplasmic IκB proteins, the atypical nuclear IκB proteins BCL‐3, IκBζ, IκBNS and IκBη were identified based on their ankyrin repeat structure through which they are able to bind NF‐κB proteins and regulate their activity . For example, IκBNS was found to bind nuclear p50, p52, p65, RelB and c‐Rel .…”
Section: Introductionmentioning
confidence: 99%
“…IκBNS is also required for normal function in other immune cells. In T cells, IκBNS mediates TCR‐induced cell death during negative selection in the thymus, governs the development of regulatory T cells through the induction of Foxp3 and is essential for cytokine production in T H 17 cells . In the myeloid lineage, IκBNS dampens the proinflammatory response through suppression of IL‐6 and IL‐12p40 production in macrophages and regulating IL‐10 production by dendritic cells upon lipopolysaccharide (LPS) stimulation …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations